Controlled synthesis of highly active Au/CeO2 nanotubes for CO oxidation. (3rd May 2017) - Wang, Zumin; Qi, Jian; Zhao, Kun; Zong, Lingbo; Tang, Zhiyong; Wang, Lianzhou; Yu, Ranbo
Abstract : High-quality Au/CeO2 nanotubes were synthesized through an oriented attachment-Ostwald ripening process and they showed excellent performance in catalytic CO oxidation. Abstract : Uniform CeO2 nanotubes with smooth thin walls and high porosity were controllably synthesized using a simple well-controlled solvothermal technique. The growth of CeO2 nanotubes was explored and it was found that it followed the oriented attachment-Ostwald ripening mechanism. Furthermore, through an auto-redox process, gold nanoparticles of ∼5 nm size could be homogeneously generated on these CeO2 nanotubes. These novel nanocomposites exhibited outstanding performance in terms of both activity and stability for catalytic CO oxidation.